Hepatoprotective Effect of Pinoresinol on Carbon Tetrachloride- Induced Hepatic Damage in Mice - Hyo-Yeon Kim; Joon-Ki Kim; Jun-Ho Choi; Joo-Yeon Jung; Woo-Yong Oh; Dong Chun Kim; Hee Sang Lee; Yeong Shik Kim; Sam Sik Kang; Seung-Ho Lee; Sun-Mee Lee (Elsevier, 2010)
Forsythiae Fructus is known to have diuretic, anti-bacterial, and anti-inflammatory activities. This study examined the hepatoprotective effects of pinoresinol, a lignan isolated from Forsythiae Fructus, against carbon tetrachloride (CCl4 )-induced liver injury. Mice were treated intraperitoneally with vehicle or pinoresinol (25, 50, 100, and 200 mg/kg) 30 min before and 2 h after CCl4 (20μl/kg) injection. In the vehicle-treated CCl4 group, serum aminotransferase activities were significantly increased 24 h after CCl4 injection, and these increases were attenuated by pinoresinol at all doses. Hepatic glutathione contents were significantly decreased and lipid peroxidation was increased after CCl4 treatment. These changes were attenuated by 50 and 100 mg/kg of pinoresinol. The levels of protein and mRNA expression of inflammatory mediators, including tumor necrosis factor-α, inducible nitric oxide synthase, and cyclooxygenase-2, were significantly increased after CCl4 injection; and these increases were attenuated by pinoresinol. Nuclear translocation of nuclear factor-κB (NF-κB) and phosphorylation of c-Jun, one of the components of activating protein 1 (AP-1), were inhibited by pinoresinol. Our results suggest that pinoresinol ameliorates CCl4-induced acute liver injury, and this protection is likely due to antioxidative activity and down-regulation of inflammatory mediators through inhibition of NF-κB and AP-1. Keywords:: carbon tetrachloride, hepatoprotective activity, inflammation, oxidative stress, pinoresinol